The expressive function of legal norms: Experimental evidence from the Supply Chain Act in Germany - Daniel Engler; Marvin Gleue; Gunnar Gutsche; Sophia Möller; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2025)
Legal norms can have a direct effect on individual behavior through their legal enforcement. However, according to the 'expressive function of law,' they can also have indirect effects on individual behavior by shaping related social norms. Since evidence for this expressive function is scarce, we consider a new law on corporate due diligence for the protection of human rights and the environment (i.e. the German Supply Chain Act) and empirically examine its indirect effects on individual sustainable purchasing behavior, as indicated by the willingness to pay (WTP) for sustainable socks, where sustainability is ensured by the certification with a label of the Fair Wear Foundation. The empirical analysis is based on data from a pre-registered and incentivized experiment implemented in a representative survey of 1,017 citizens in Germany. Before making socks purchasing decisions and the elicitation of related personal injunctive and perceived social norms, the respondents were randomly assigned to either a control group or a treatment group that received information about the German Supply Chain Act. We examine average treatment effects and, based on a causal mediation analysis, the mediating role of related personal injunctive and perceived social norms on individual sustainable purchasing behavior. A manipulation check shows that the treatment information has a significantly positive effect on individual knowledge about the objectives of the German Supply Chain Act. However, the treatment information has no significant effect on the WTP for sustainable socks with the Fair Wear Foundation label or on related norms. Although our mediation analysis reveals that personal injunctive and perceived social norms are significantly positively correlated with this WTP, our experimental analysis does not provide any evidence for the expressive function of law in the case of the German Supply Chain Act and individual sustainable purchasing behavior.
Keywords: D91; K38; Q58; 330; Legal norms; Personal injunctive norm; Perceived social norms; German Supply Chain Act; Individual sustainable purchasing behavior